2021
DOI: 10.1177/1479973121994783
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the changing rehabilitation needs of patients undergoing thoracic surgery

Abstract: The rehabilitation needs of individuals undergoing thoracic surgery are changing, especially as surgical management is increasingly being offered to patients who are at risk of developing functional limitations during and after hospital discharge. In the past rehabilitative management of these patients was frequently limited to specific respiratory physiotherapy interventions in the immediate postoperative setting with the aim to prevent postoperative pulmonary complications. In the past two decades, this focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 103 publications
0
10
1
Order By: Relevance
“…Literature on interventions to improve physical activity in LTx recipients is scarce. 2 Improvements in daily steps in the current study exceeded those shown following exercise training. 10 , 38 This is likely due to step counts being the central focus of the intervention and the incorporation of behavioural techniques such as self-monitoring, goal setting and feedback, which have been deemed important for enhancing healthy activity behaviours.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Literature on interventions to improve physical activity in LTx recipients is scarce. 2 Improvements in daily steps in the current study exceeded those shown following exercise training. 10 , 38 This is likely due to step counts being the central focus of the intervention and the incorporation of behavioural techniques such as self-monitoring, goal setting and feedback, which have been deemed important for enhancing healthy activity behaviours.…”
Section: Discussioncontrasting
confidence: 54%
“… 1 In addition to increasing survival, an important goal of LTx is to enhance health-related quality of life (HRQoL) and physical function. 2 Despite improvements in lung function, significant skeletal muscle weakness and reduced exercise capacity persist after LTx, which may limit improvements in daily physical functioning and HRQoL. 3 This is due to a host of factors including deconditioning as a result of persistent sedentary time, as well as immunosuppressant medications and episodes of organ rejection which may hinder functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A narrative review by Daniel Langer summarizes the landscape of rehabilitation in thoracic surgery focusing on interventions that aim to optimize physical function pre-operatively and recovery in the post-operative period. 3 This review highlights that the majority of the evidence is in the areas of thoracic oncology and lung transplantation. It also reinforces that rehabilitation programs can be beneficial in improving skeletal muscle function, exercise capacity, quality of life, and functional recovery, but there remains a lack of guidelines with respect to training regimens, duration and referral pathways.…”
mentioning
confidence: 99%
“… 6 Pre-operative physical function can help with earlier post-operative mobilization, improved airway clearance and ventilatory mechanics that can help reduce postoperative pulmonary complications. 3 , 7 …”
mentioning
confidence: 99%
See 1 more Smart Citation